Motnje funkcije čutil v starosti in njihov pomen za sposobnost funkcioniranja starostnika - Kos, Nataša (Rehabilitacija (Ljubljana), 2012)
We see, hear, smell, taste and touch the environment. In addition to the sensory organs, normal functioning of the brain is also essential for the sensory processes. The process of aging begins at birth and continues throughout life. As we age, our senses become less accurate and we may have trouble distinguishing details. Because of the sensory changes, we have problems with communication, involvement in activities and social interaction. That can contribute to a sense of isolation, lead to loneliness and feelings of depression and also to dependence in performing basic and especially instrumental activities of daily living. The paper describes sensory changes and their impact on functioning. Possible adaptations of the environment to compensate for age-related sensory losses, necessary for maintaining independent living in the older age, are outlined.
Keywords: Aging; čutila; fiziologija; functioning; funkcioniranje; independence; samostojnost; senses; staranje; starostniki